2013
DOI: 10.1038/ismej.2013.161
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated transporter activity shapes high-affinity iron acquisition in cyanobacteria

Abstract: Iron bioavailability limits biological activity in many aquatic and terrestrial environments. Broad scale genomic meta-analyses indicated that within a single organism, multiple iron transporters may contribute to iron acquisition. Here, we present a functional characterization of a cyanobacterial iron transport pathway that utilizes concerted transporter activities. Cyanobacteria are significant contributors to global primary productivity with high iron demands. Certain cyanobacterial species employ a siderop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
130
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 60 publications
1
130
0
Order By: Relevance
“…Fe 0 may be able to enter the cells by passive transport via OM porins at a very low rate, but the majority would be absorbed by energy-coupled active transport. As it crosses the OM, Fe 0 maybe reduced in the periplasmic space before transport across the cyanobacterial plasma membrane (Kranzler et al, 2011(Kranzler et al, , 2014. The findings in the present study provide new insights into the iron acquisition pathway of photosynthetic cyanobacteria in aqueous environments.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Fe 0 may be able to enter the cells by passive transport via OM porins at a very low rate, but the majority would be absorbed by energy-coupled active transport. As it crosses the OM, Fe 0 maybe reduced in the periplasmic space before transport across the cyanobacterial plasma membrane (Kranzler et al, 2011(Kranzler et al, , 2014. The findings in the present study provide new insights into the iron acquisition pathway of photosynthetic cyanobacteria in aqueous environments.…”
Section: Discussionmentioning
confidence: 58%
“…As many cyanobacterial species other than Synechocystis 6803 do not excrete siderophores, the importance of siderophore-mediated iron uptake in cyanobacteria has been questioned. Hopkinson and Morel (2009) and Kranzler et al (2011Kranzler et al ( , 2014 suggested that cyanobacteria probably use uptake pathways involving a reduction step, rather than direct internalization of siderophores and other iron chelates. We hypothesize that organic chelators such as siderophores may provide iron pools, which maintain iron solubility and recruit iron in dilute water environments, while cyanobacteria prefer free iron and efficiently sequester it with high rate via TonB-ExbB-ExbD-dependent active transport system (see a hypothesized model shown in Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, they undergo major architectural changes in photosynthetic membranes involving the over-expression of photosynthetic pigments (Ryan-Keogh et al, 2012), the use Fe-economic pathways for ATP synthesis (Bailey et al, 2008), and the reduction of their Fe requirements (Behrenfeld and Milligan, 2013). In addition, some cyanobacteria have also developed specific high-affinity Fe uptake strategies (Morrissey and Bowler, 2012;Kranzler et al, 2014) such as production of siderophores that enhance Fe bioavailability in their immediate environment (Sunda, 2012). Thus, these complex biological interactions with Fe chemistry challenge the quantification of Fe bioavailability in marine environments.…”
Section: Introductionmentioning
confidence: 99%